Ultrasound-guided neuromonitoring methods in the intensive care unit - Demir, Ufuk; Taşkın, Öztürk; Doğanay, Zahide (MediHealth Academy, 2023)
Ultrasonography (USG) is a non-invasive, portable, bedside, reproducible, radiation-free, inexpensive, and easily accessible imaging method. It provides morphological and functional information. It allows for diagnosis, monitoring, and guiding treatment. The usage areas of USG in the ICU are broad. In interventional procedures (thoracentesis, vascular interventions, percutaneous tracheostomy), evaluation of lung pathologies (pneumothorax, pleural effusion, pulmonary edema, consolidation, A-line, B line), diaphragm evaluation, abdominal imaging (trauma, kidney, liver), diagnosis and follow-up of deep vein thrombosis and the assessment and follow-up of fluid resuscitation (IVCI) and neuromonitoring. USG-guided neuromonitoring can detect stenosis or occlusion of intracranial arteries, monitor the development of patients with vasospasm after subarachnoid hemorrhage, detect cerebral embolism, evaluate the cerebral collateral system, and determine brain death. It can also indirectly calculate intracranial pressure (ICP) and cerebral perfusion under USG guidance.
Keywords: 3. Good health